2021
DOI: 10.48550/arxiv.2108.07260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reassessing the Limitations of CNN Methods for Camera Pose Regression

Tony Ng,
Adrian Lopez-Rodriguez,
Vassileios Balntas
et al.

Abstract: In this paper, we address the problem of camera pose estimation in outdoor and indoor scenarios. In comparison to the currently top-performing methods that rely on 2D to 3D matching, we propose a model that can directly regress the camera pose from images with significantly higher accuracy than existing methods of the same class. We first analyse why regression methods are still behind the state-of-the-art, and we bridge the performance gap with our new approach. Specifically, we propose a way to overcome the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…CNN use absolute camera pose regression (APR) techniques to predict the camera pose of an input image [118] by implicitly expressing a scene using network weights. They adhere to the same process: a base network extracts the absolute features [119] that are then embedded in a high-dimensional space.…”
Section: ) Absolute Camera Pose Regressionmentioning
confidence: 99%
“…CNN use absolute camera pose regression (APR) techniques to predict the camera pose of an input image [118] by implicitly expressing a scene using network weights. They adhere to the same process: a base network extracts the absolute features [119] that are then embedded in a high-dimensional space.…”
Section: ) Absolute Camera Pose Regressionmentioning
confidence: 99%
“…Naseer and Burgard [26] showed that RGB-D data can be exploited to generate additional views from the limited training images to improve performance. Recently, Ng et al [27] and Moreau et al [15] extended this idea to RGB data. Other works propose to use additional information often available in robotic applications [11], [13].…”
Section: Related Workmentioning
confidence: 99%
“…Camera pose prediction typically involves estimating the relationship between two consecutive datasets with six degrees of freedom (DoF) [76][77][78][79]. The primary 2D-planebased loss function, as discussed earlier, acts as the central mechanism for training the camera pose prediction algorithm, while the extended loss function indirectly addresses occlusions resulting from obscured objects.…”
Section: Self-supervised Loss Functions Including Depth Consistencymentioning
confidence: 99%
“…In the field of unsupervised monocular depth prediction, incorporating a camera pose network is crucial for determining the relative positions of cameras [7][8][9][10][11]. A significant challenge in this area has been achieving accurate six degrees of freedom (DoF) camera pose predictions [76][77][78][79]. Two principal methodologies have been explored: one method inputs moving objects and depth data directly, while the other utilizes a visual odometry algorithm based on a distinct mathematical function [9].…”
Section: Camera Pose Estimationmentioning
confidence: 99%